2020
DOI: 10.1186/s12913-020-05868-1
|View full text |Cite
|
Sign up to set email alerts
|

At the intersection of precision medicine and population health: an implementation-effectiveness study of family health history based systematic risk assessment in primary care

Abstract: Background Risk assessment is a precision medicine technique that can be used to enhance population health when applied to prevention. Several barriers limit the uptake of risk assessment in health care systems; and little is known about the potential impact that adoption of systematic risk assessment for screening and prevention in the primary care population might have. Here we present results of a first of its kind multi-institutional study of a precision medicine tool for systematic risk as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…These findings are similar to what has been observed when implementing standardized risk assessment within the primary care environment. In those studies, a significant proportion of the population was found to be at risk for hereditary cancer syndromes [27,30,34,40] (though lower than in a population pre-selected for having breast cancer as in this study) but as in this study, while there is some uptake of risk recommendations, there remain challenges to be addressed to improve clinical impact [32,41].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These findings are similar to what has been observed when implementing standardized risk assessment within the primary care environment. In those studies, a significant proportion of the population was found to be at risk for hereditary cancer syndromes [27,30,34,40] (though lower than in a population pre-selected for having breast cancer as in this study) but as in this study, while there is some uptake of risk recommendations, there remain challenges to be addressed to improve clinical impact [32,41].…”
Section: Discussionmentioning
confidence: 69%
“…MeTree, a web-based patient-facing FHH collection software with integrated clinical decision support (CDS), is one such platform [31]. MeTree has been extensively studied in primary care where it has been shown to increase risk identification and impact clinical care [32][33][34]. We sought to evaluate how MeTree might be used to meet the needs of an oncology setting.…”
Section: Introductionmentioning
confidence: 99%
“…With the potential health impact of a systematic risk assessment becoming increasingly evident, the need for access to such services is more apparent than ever [11,27,53]. However, access alone is insufficient to ensure an optimal patient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…MeTree has been evaluated in numerous healthcare systems in the United States and in Singapore [23][24][25]. It has been widely accepted in primary care populations and significantly increases the identification of individuals at risk for hereditary conditions [24,26,27].…”
Section: Interventionmentioning
confidence: 99%
“…To be an effective risk assessment tool, family history must be accurately collected and interpreted by clinicians, and clinical recommendations should be discussed with patients. Common barriers to obtaining family history from the clinician’s perspective include time required to obtain history (15–30 minutes), lack of reimbursement for time, and providers’ perceived limitations to counsel on heritable findings [ 23 ] (see Supplementary Table 1 for additional references). Patient-facing web tools for family history collection have demonstrated superior data quality and completeness compared with traditional in-person collection, and improved the accuracy of risk stratification for other diseases [ 24 ].…”
Section: Genomic-guided Risk Stratification For Admentioning
confidence: 99%